Relative nutritional value of whole protein, hydrolysed protein and free amino acids in man. Issue 7 (July 1985) - Moriarty, K J; Hegarty, J E; Fairclough, P D; Kelly, M J; Clark, M L; Dawson, A M
Abstract : To compare their effects on nitrogen balance, diets containing either lactalbumin whole protein, its peptide-rich enzymic hydrolysate or an equivalent mixture of free amino acids as the sole source of dietary nitrogen were fed to two healthy subjects, each studied for 38 days on two separate occasions. The nitrogen intake (47 mg/kg body wt/day) induced a state of negative nitrogen balance, stimulating nitrogen conservation. Net daily nitrogen balance (mean +/- SD) in subject 1 was -0.23 +/- 0.72 g (amino acids) vs + 0.05 +/- 0.52 g (protein) and -0.21 +/- 0.58 g (amino acids) vs -0.05 +/- 0.57 g (hydrolysate), and in subject 2, -0.19 +/- 0.60 g (amino acids) vs -0.16 +/- 0.51 g (protein) and -0.42 +/- 0.35 g (amino acids) vs -0.62 +/- 0.34 g (hydrolysate). Analysis of these results by the cumulative sum technique showed no significant differences in the effect of the three nitrogen sources on nitrogen balance. This study indicates that there is no nutritional evidence to support the current practice of prescribing expensive enteral diets containing peptides or amino acids rather than the much cheaper whole protein to patients with normal gastrointestinal function.